2010
DOI: 10.1029/2010gc003262
|View full text |Cite
|
Sign up to set email alerts
|

Crystal fractionation processes at Baru volcano from the deep to shallow crust

Abstract: [1] Linking shallow and deep crustal processes at volcanic arcs is an important component in evaluating the growth and evolution of the continental crust. Commonly, deep crustal processes and the nature of subarc lithosphere are studied long after the volcanism has ceased in obducted arc terranes. In active arcs, studies of deep crustal processes focus on cumulates derived from middle-lower crustal levels. Although uncommon in the erupted magmas, these cumulates are required by crustal differentiation models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 153 publications
(175 reference statements)
0
37
0
Order By: Relevance
“…These experimental studies along with studies of natural samples (Grove and Donnelly-Nolan 1986;Romick et al 1992;Davidson et al 2007) have shown that amphibole crystallizes from a wide variety of liquids at crustal pressures and can be an important fractionating phase in arc systems. Significant amphibole fractionation has been inferred to occur at arcs such as Panama (Hidalgo and Rooney 2010), Chile (Kratzmann et al 2010), and globally (Davidson et al 2007). Olivine-bearing, plagioclase-free amphibole cumulates have been identified in the Bonanza Jurassic arc in British Columbia (Larocque and Canil 2010), and the Adamello batholith (Tiepolo et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…These experimental studies along with studies of natural samples (Grove and Donnelly-Nolan 1986;Romick et al 1992;Davidson et al 2007) have shown that amphibole crystallizes from a wide variety of liquids at crustal pressures and can be an important fractionating phase in arc systems. Significant amphibole fractionation has been inferred to occur at arcs such as Panama (Hidalgo and Rooney 2010), Chile (Kratzmann et al 2010), and globally (Davidson et al 2007). Olivine-bearing, plagioclase-free amphibole cumulates have been identified in the Bonanza Jurassic arc in British Columbia (Larocque and Canil 2010), and the Adamello batholith (Tiepolo et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Most arc lavas are highly differentiated and have mineral assemblages that are the product of shallow, relatively late crystallization processes (Davidson et al, 2007). Here we consider minerals other than those observed in erupted lavas as a possible control on Th/U ratios, including cryptic mineral fractionation in the mid-to lower-crust (e.g., Lee et al, 2006;Davidson et al, 2007;Hidalgo and Rooney, 2010). Although an uncommon eruptive product, garnet is observed where the lower crustal roots of arcs are exposed.…”
Section: Th-excess Generated From Cryptic Garnet Fractionation Inmentioning
confidence: 97%
“…Although an uncommon eruptive product, garnet is observed where the lower crustal roots of arcs are exposed. Deep garnet fractionation imparts distinct chemical signatures on magmas, including HREE depletions, unusually high Sr/Y ratios, moderate Fe/Mg ratios, and, as a result of an affinity for U relative to Th (D U = 0.31, D Th = 0.074; Rubatto and Hermann, 2007), significant 230 Th-excesses may be produced (Ankney et al, 2013;Hidalgo and Rooney, 2010;Jicha et al, 2009b).…”
Section: Th-excess Generated From Cryptic Garnet Fractionation Inmentioning
confidence: 99%
“…This process is possible as thermal models indicate that temperatures above the aqueous fluid saturated solidus are common along the top of most subducting plates worldwide (Conder, 2005;Kelemen et al, 1990;van Keken, Kiefer, et al, 2002;Peacock et al, 2005). Lower crustal fractionation (Hidalgo & Rooney, 2010;Hidalgo & Rooney, 2014) and/or anatexis of lower crust materials (Vogel et al, 2004) will later add to the evolution of primary magmas into even more felsic compositions. Lower crustal fractionation (Hidalgo & Rooney, 2010;Hidalgo & Rooney, 2014) and/or anatexis of lower crust materials (Vogel et al, 2004) will later add to the evolution of primary magmas into even more felsic compositions.…”
Section: 1029/2018gc008128mentioning
confidence: 99%